Partial derivatives

Calculus Level 4

Find δ w δ x \frac { \delta w }{ \delta x } at the point ( x , y , z ) = ( 2 , 1 , 1 ) (x,y,z)=(2,-1,1) if w = x 2 + y 2 + z 2 w={ x }^{ 2 }+{ y }^{ 2 }+{ z }^{ 2 } , z 3 x y + y z + y 3 = 1 { z }^{ 3 }-xy+yz+{ y }^{ 3 }=1 , and x x and y y are the independent variables.


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Jun 12, 2015

It is given that:

{ w = x 2 + y 2 + z 2 z 3 x y + y z + y 3 = 1 { w x = 2 x + 2 z z x . . . ( 1 ) 3 z 2 z x y + y z x = 0 . . . ( 2 ) \begin{cases} w = x^2+y^2+z^2 \\ z^3-xy+yz+ y^3 = 1 \end{cases} \Rightarrow \begin{cases} \dfrac {\partial w} {\partial x} = 2x+2z \dfrac {\partial z} {\partial x} & ...(1) \\ 3z^2\dfrac {\partial z} {\partial x} -y+y\dfrac {\partial z} {\partial x} = 0 & ... (2) \end{cases}

Substituting x = 2 x=2 , y = 1 y=-1 and z = 1 z=1 in Eq. 2:

3 ( 1 ) z x ( 1 ) + ( 1 ) z x = 0 2 z x + 1 = 0 z x = 1 2 \begin{aligned} 3(1)\frac {\partial z} {\partial x} -(-1)+(-1)\frac {\partial z} {\partial x} & = 0 \\ 2\frac {\partial z} {\partial x} + 1 & = 0 \\ \Rightarrow \frac {\partial z} {\partial x} & = -\frac{1}{2} \end{aligned}

From Eq. 1: w x = 2 ( 2 ) + 2 ( 1 ) ( 1 2 ) = 3 \begin{aligned} \frac {\partial w} {\partial x} & = 2(2)+2(1) \left( -\frac {1} {2} \right) = \boxed{3} \end{aligned}

Moderator note:

Simple standard approach.

{ w = x 2 + y 2 + z 2 z 3 x y + y z + y 3 = 1 { w x = 2 x + 2 z z x . . . ( 1 ) 3 z 2 z x y + y z x = 0 . . . ( 2 ) z x = y 3 z 2 + y . . . ( 3 ) E l i m i n a t i n g z x from (1) and (3), and substituting for (x,y,z), w x = 2 x + 2 z y 3 z 2 + y = 2 2 + 2 1 1 3 1 2 1 = 3 \begin{cases} w = x^2+y^2+z^2 \\ z^3-xy+yz+ y^3 = 1 \end{cases} \Rightarrow \begin{cases} \dfrac {\partial w} {\partial x} = 2x+2z \dfrac {\partial z} {\partial x} & ...(1) \\ 3z^2\dfrac {\partial z} {\partial x} -y+y\dfrac {\partial z} {\partial x} = 0 & ... (2)\\\therefore~ \dfrac {\partial z} {\partial x} =\dfrac y { 3z^2+y} & ...(3) \end{cases} \\Eliminating ~~\dfrac{\partial z}{\partial x} ~\text{from (1) and (3), and substituting for (x,y,z),}\\\dfrac {\partial w} {\partial x}=2x+2z*\dfrac y { 3z^2+y} =2*2+2*1*\dfrac {-1}{3*1^2-1} =~~~~ \large \color{#D61F06}{3}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...